Design and in vivo verification of a stress radiography device towards it's suitability for multi-ligament laxity measurements - Beukes, Giancarlo (Division of Biomedical Engineering, 2018)
The human knee is a hinge joint, primarily facilitating locomotion. Knee joint instability, due to ligament injuries, is a result of direct or indirect trauma, non-anatomical stresses during pivoting movements about the knee, imbalanced landing during jumping and rapid deceleration during high intensity locomotion. Biomechanical indications of an unstable knee joint include decreased joint integrity, hyperlaxity, abrupt locking and catching combined with clicking noises during locomotion. Approximately, two hundred and fifty thousand ACL injuries occur in the United States of America annually. Current diagnostic procedures are subjective according to the clinician's experience. This potentially leads to misdiagnosis of the injury and improper treatment. Non-invasive diagnostic techniques make use of manual methods, MRI and laxity measurement devices (e.g. arthrometers and stress radiography devices). Laxity measurement devices (the focus of this study) determine ligament health by measuring their elasticity and stiffness. Directional tibial and fibular bone translation is induced by applying an external load to the joint. The bone translation is measured in relation to the load applied, which denotes ligament laxity. The Laxmeter is a novel, cost effective and radiolucent multi-ligament laxity measurement stress radiography device. This device facilitates the measurement of MCL and LCL laxity at multiple degrees of knee joint flexion, however, it lacks the essential means to perform the laxity measurement technique. The current study aims to redesign the Laxmeter to perform ACL, PCL, MCL and LCL laxity measurement procedures at multiple fixed degrees of knee joint flexion. The in vitro functional verification of the device was limited to (according to scope) a single cadaver trial; to validate functionality, structural integrity, usability as well as demonstrate the Laxmeter concept prior to a prospective full clinical trial. The redesigned Laxmeter Prototype consists of a load applicator capable of applying a 250N load to various aspects of the proximal lower leg, to induce bone translation for laxity measurements. The load applicator is designed to integrate with the ergonomic patient support structure, the later potentially improving reproducibility and accuracy of the laxity measurement results. The cadaver trial demonstrated the device's capability of measuring the laxity of the ACL, MCL and LCL at predetermined knee flexion angles. To measure the ligament laxity, equal loads were applied to both proximal lower limbs independently. The bilateral average displacement of the tibia with respect to the femur for each ligament was noted. In the case of the ACL, the Laxmeter measured an average laxity of 3.07mm at 30° knee flexion and a load of 150N. The average laxities for the MCL and LCL at 30° knee flexion and 150N were 1.11mm and 2.02mm. The trial yielded preclinical results that were comparable with existing clinical and healthy cadaver based studies (using similar techniques), and suggests that the Laxmeter is capable of measuring the laxity of the ACL, MCL and LCL at various degrees of knee flexion. PCL laxity measurements could not be performed due to compromised structural integrity, which was essential to make the Laxmeter portable and lightweight. Future recommendations for the device include rotational ankle fixation; improved overall limb fixation; improved structural integrity to allow for PCL laxity measurements as well as further preclinical (functional) verification procedures prior to a full clinical trial.